Case Report: Functional Analysis and Neuropsychological Evaluation of Dyshormonogenetic Fetal Goiter in Siblings Caused by Novel Compound Hyterozygous TPO Gene Mutations - Rodrigues, Tania Maria Barreto; Silva, Marlon Messias da Conceição; Freitas, Magali Maciel; Duarte, Zélia Maria Costa; Frutuoso, Vitória Sousa; Rodrigues, Mariana Teixeira; Rubio, Ileana Gabriela Sanchez (Frontiers in Endocrinology, 2021)
It is rare for a euthyroid mother to carry a child with a fetal goiter. However, cases of congenital hypothyroidism (CH) caused by thyroid dyshormonogenesis have been reported. Even though gene mutations associated with fetal goiter have been reported in few studies, the effects on intellectual development have not been investigated. This study aimed to characterize and investigate the underlying genetic mechanism of CH and neuropsychological development and growth of two siblings with CH-induced fetal goiters. Case report: Two male siblings from a nonconsanguineous marriage with CH and fetal goiter diagnosed by ultrasonography at 32- and 26-weeks of gestation. This condition was confirmed by cordocentesis in the first pregnancy (TSH: 135 μUI/mL). The mother was euthyroid, and no intra-amniotic levothyroxine treatment was performed. Peripheral blood DNA was screened for TPO mutations. The new deletion p.Cys296Alafs*21 and the p.Arg665Trp mutation were identified in both patients, inherited from heterozygous parents. Functional analysis showed both mutations reduced the TPO enzyme activity and impaired the membrane localization. The p.Cys296Alafs*21 mutation produces a protein product with a drastically reduced molecular weight. Additionally, a complete clinical and neuropsychological evaluation was also performed. The WISC IV test was employed to provide an overall measure of the siblings' cognitive and intellectual abilities. No growth retardation was detected in either child. In general, both children showed a normal neuropsychological development, however, they exhibited slight reduction of Processing Speed Index scores, which are sensitive to neurological and attentional factors and motor maturation activity. Notably, the younger sibling obtained significantly low scores in the Operational Memory Index, a measure of attention capacity and psychoneurological immaturity. Conclusion: We described a new TPO compound heterozygosity that severely impaired the TPO activity and membrane localization leading to severe CH and fetal goiter. This is the first report showing the neuropsychological evaluation in patients with dyshormonogenetic fetal goiter. More studies are needed to understand the neurodevelopmental outcomes of neonates with CH-induced fetal goiters.